Ulcerative Colitis of the Appendix (‘Ulcerative Appendicitis’) Mimicking Acute Appendicitis - LR Barclay; WT Depew; KK Taguchi; DJ Hurlbut (Canadian Journal of Gastroenterology)
Appendiceal involvement in ulcerative colitis may occur in the setting of either diffuse or distal disease, and is usually diagnosed incidentally at the time of proctocolectomy. The present patient had a rare case of 'ulcerative appendicitis' occurring on a background of clinically quiescent ulcerative colitis, and presented with the signs and symptoms of acute appendicitis.